Role of estuarine natural flocculation process in removal of Cu, Mn, Ni, Pb and Zn - S. Hassani; A.R. Karbassi; M. Ardestani (Global Journal of Environmental Science and Management)
The ﬂocculation of dissolved heavy metals is a process which has an important effect on decreasing the concentration of the colloidal elements during estuarine mixing of river water and sea or ocean water. During this important process, a large amount of colloidal elements change into particles in the form of flock and the dissolved loads decline. This study is performed to evaluate the mechanism of self-purification of heavy metals in Sardabroud's estuary. For this purpose, the effect of salinity (varying from 1 to 8.5‰) on the removal efficiency of colloidal metals (copper, zinc, lead, nickel and magnesium) by flocculation process during mixing of Sardabroud River water and the Caspian Sea water was explored. The flocculation rate of Ni (25%) > Zn (18.59%) > Cu (16.67%) > Mn(5.83%) > Pb(4.86%)  indicates that lead and manganese have relatively conservative behavior but nickel, zinc and copper have non-conservative behavior during Sardabroud River’s estuarine mixing. The highest removal efficiencies were obtained between salinities of 1 to 2.5%. Due to flocculation process, annual discharge of dissolved zinc, copper, lead, manganese and nickel release into the Caspian Sea via Sardabroud River would reduce from 44.30 to 36.06 ton/yr, 3.41 to 2.84 ton/yr, 10.22 to 9.7 ton/yr, 8.52 to 7.8 ton/yr and 3.41 to 2.56 ton/yr, respectively. Statistical analysis shows that the flocculation rate of Nickel is highly controlled by redox potential and dissolved oxygen. Moreover, it is found that total dissolved solid, salinity, electrical conductivity and potential of hydrogen do not have a significant influence in flocculation of studied metals.